Assessment of Knowledge and Readiness for the Diagnosis and Management of Preeclampsia among Healthcare Workers from Selected Healthcare Facilities in Lusaka, Zambia - Mwansa, Pamela; Daniel, Ebenezer Obi; Akpan, Ubong; Mwansa, Hope (International Journal of Innovative Research in Medical Science, 2021)
Preeclampsia (PE) is the leading cause of maternal and perinatal morbidity/mortality. A study in Lusaka estimated Preeclampsia/Eclampsia prevalence at 18.9%. The aim of the study was to assess knowledge and readiness for the diagnosis and management of Preeclampsia among healthcare workers from selected healthcare facilities in Lusaka, Zambia. An observational cross-sectional study was used to assess healthcare workers knowledge and adherence to diagnosis and management of PE in the selected facilities. Semi-structured interviewer administered questionnaires and an observational checklist were used amongst the respondents. Health facility data was available from a total of 5 public health facilities (PHCs), 1 higher public and 4 Level one facilities. Of all the 41 interviewed health personnel, all (100%) agreed they checked for blood pressure in assessment for preeclampsia. The lowest responses, 1(7%) and 1(4.8) between specialists and nurses was recorded in assessment of consciousness as most did not respond to it. staff nurses had poorer knowledge related to management of preeclampsia and most of the differences were statistically highly significant (p < 0.001). in terms of readiness for PE diagnosis and management, drugs and supplies were found to be good in all health facilities with more than 70% except Chipata clinic (57%) which indicated readiness to be poor. The facility audits revealed gaps in the availability of certain key equipment, drugs and supplies as well as lack of proper infrastructure especially at Chipata clinic. The study revealed that knowledge gaps exist among health workers especially the nurses in the initial assessment for preeclampsia such as checking for consciousness by health personnel. Most drugs were readily available but some equipment and infrastructure were lacking in the facilities. In terms of PE/E management, the correct dosage of magnesium sulphate and maintenance dosage were administered.